2011
DOI: 10.1063/1.3624590
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gas-flow-induced voltage in graphene

Abstract: We show by systemically experimental investigation that gas-flow-induced voltage in monolayer graphene is more than twenty times of that in bulk graphite. Examination over samples with sheet resistances ranging from 307 to 1600 Ω/sq shows that the induced voltage increase with the resistance and can be further improved by controlling the quality and doping level of graphene. The induced voltage is nearly independent of the substrate materials and can be well explained by the interplay of Bernoulli's principle … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…13 and the trend in monolayer graphene as reported in our previous work, 14 the gas-flow-induced voltage is proportional to the square of the Mach number, where M = v/c, v is the gas flowvelocity, and c is the sound velocity in medium (353m/s for nitrogen at 300 K), and separating into two linear regions with different slopes. However, the slope in the high velocity region with M 2 > 0.06 is larger than that in the low velocity region with M 2 < 0.06 for all the samples with bi-to octa-layer, in sharp contrast with the trend reported previously that the slope in the high velocity region is lower 13,14.…”
contrasting
confidence: 96%
See 1 more Smart Citation
“…13 and the trend in monolayer graphene as reported in our previous work, 14 the gas-flow-induced voltage is proportional to the square of the Mach number, where M = v/c, v is the gas flowvelocity, and c is the sound velocity in medium (353m/s for nitrogen at 300 K), and separating into two linear regions with different slopes. However, the slope in the high velocity region with M 2 > 0.06 is larger than that in the low velocity region with M 2 < 0.06 for all the samples with bi-to octa-layer, in sharp contrast with the trend reported previously that the slope in the high velocity region is lower 13,14.…”
contrasting
confidence: 96%
“…13 We previously found that the gas-flow-induced voltage in monolayer graphene is twenty-folds over that in bulk graphite, although the Seebeck coefficient of monolayer graphene is about 6 times of that of bulk graphite. 14 Recently, unique properties, including thermal properties of multilayer graphene have been revealed. 11,15,16 The structure of the low-energy electronic dispersion is linear for monolayer graphene, 17 while in bilayer graphene, the shape of the energy bands is quadratic 18 and becomes cubic in ABC-stacked trilayer.…”
mentioning
confidence: 99%
“…As the semiconductor materials are promising for waste-heat recovery, the graphene has been also studied [11]. Gas flow sensor with the use of Seebeck effect and its correlation with Bernoulli law was presented for single layer graphene [12] and multilayer graphene [13]. These results demonstrate that graphene has great potential for flow sensors and energy conversion devices.…”
Section: Introductionmentioning
confidence: 93%
“…[5,11,12] Flows of nonpolar gases such as argon, nitrogen, and oxygen over CNTs at the speed of af ew meters per second can also generate voltage and current;t he underlying mechanism is assumed to be an interplay between Bernoullis principle and the Seebeck effect. [13,14] Additionally,e nvironmental humidity change has proved to produce transient potential in different approaches. [15][16][17][18] However,a lmost all the above-mentioned energy-generation strategies are attributed to liquid/gas flow or changes in environmental con-ditions.H erein we report that electrical potential can be induced by an atural and ubiquitous phenomenon, namely vapor adsorption, by manipulation of the proton-donating functional groups on apiece of porous carbon film (PCF).…”
mentioning
confidence: 99%